Towards synchrotron phase-contrast lung imaging in patients: a proof-of-concept study on porcine lungs in a human-scale chest phantom - Wagner, Willi Linus; Wünnemann, Felix; Biederer, Jürgen; Konietzke, Philip; Stiller, Wolfram; Wielpütz, Mark Oliver; Kauczor, Hans-Ulrich (Journal of synchrotron radiation, 2018)
This proof-of-concept study on a human-scale chest phantom and fresh porcine lungs with artificial pulmonary nodules demonstrates that local-area in-line free propagation phase-contrast synchrotron tomography of fresh porcine lungs can be performed with an acceptable X-ray dose that would allow for future application in patients while providing spatial-resolution magnitudes higher than currently available clinical computed tomography scanners.
Gesehen am 16.04.2019